2020
DOI: 10.3390/ma13235576
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mechanical Properties and Durability of Alkali-Activated Coal Gangue-Slag Concrete

Abstract: Herein, a new geopolymer is recognized as a potential alternative cementing material of ordinary Portland cement (OPC), which is used for reducing carbon emissions and efficiently recycling the waste. Therefore this paper mainly studied the alkali-activated coal gangue-slag concrete (ACSC) was prepared by using the coal gangue-slag and Na2SiO3 and NaOH complex activator. The ratio of coal gangue (calcined and uncalcined) coarse aggregate replacing the gravel was 0%, 30%, 50%, 70%, and 100%. The water and salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The LN 2 jet is shot radially from the main borehole into multiple branches to create a complex lateral fracture network (Figure ). The casing is run vertically, the well is cemented, and the tubing and deflector are lowered into the vertical wellbore . The deflector is anchored to the target layer, and the nozzles for the high-pressure hose and the coiled tubing are introduced into the hole.…”
Section: Ln2 Fracturing Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The LN 2 jet is shot radially from the main borehole into multiple branches to create a complex lateral fracture network (Figure ). The casing is run vertically, the well is cemented, and the tubing and deflector are lowered into the vertical wellbore . The deflector is anchored to the target layer, and the nozzles for the high-pressure hose and the coiled tubing are introduced into the hole.…”
Section: Ln2 Fracturing Processesmentioning
confidence: 99%
“…The casing is run vertically, the well is cemented, and the tubing and deflector are lowered into the vertical wellbore. 185 The deflector is anchored to the target layer, and the nozzles for the high-pressure hose and the coiled tubing are introduced into the hole. The abrasive LN 2 is pumped to the drill side through the nozzle.…”
Section: Mechanisms Of Ln 2 Fracturingmentioning
confidence: 99%
“…Ma H. et al studied the effect of slag on the strength of coal gangue-based geopolymer samples and found that the compressive strength of coal gangue-based geopolymer samples with 50% slag content increased rate was 55.98% [ 16 ]. Zhu H. et al measured the compressive strength of coal gangue slag concrete and mixed coal gangue and slag as binder with sand to prepare geopolymer concrete with compressive strength of 62.1 MPa at 28 days [ 17 ]. Gao X. et al mixed coal gangue with 60% mineral powder, and the compressive strength of coal-gangue-based geopolymer could reach 51.7 MPa at 28 days [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the classic Aas-Jakobsen fatigue life equation [14], Yu et al [15] established the equations for determining the freeze-thaw fatigue damage in concrete subjected to water freeze-thaw and salt freeze-thaw conditions, and Tian et al [16] proposed a prediction model for the degree of damage caused to concrete when subjected to salt freeze-thaw and flexural load combined. In addition, some classic and well-known mathematical functions or equations are often used to characterize freeze-thaw damage to concrete, such as the parabolic function [17], the Boltzmann equation [18], the inverse logistic function [19], the power function [20] and the exponential function [21].…”
Section: Introductionmentioning
confidence: 99%